1996
DOI: 10.1136/fn.75.2.f87
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased red cell mass on subclinical tissue acidosis in hyaline membrane disease.

Abstract: Aim-To determine whether there are subclinical deficits in oxygen delivery in ventilated premature neonates. Method-Ventilated premature neonates weighing less than 1500 g, who were transfused for anaemia or who were given colloids for clotting abnormalities (or oedema), were haemodynamically monitored during the first week of life. Calf muscle surface pH (tpH) was measured in conjunction with peripheral limb blood flow by occlusion plethysmography. Results-Packed red blood cell transfusions corrected a subcli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…[16] This agrees with a previous study that suggests that packed RBCs increase regional oxygen delivery and tissue surface pH. [17] This was relevant clinically in our study when we observed a statistically significant decrease in the heart rate of our infants after transfusion, suggesting that this decrease in heart rate was most probably explained by the migitation of tissue hypoxia and concomitant tachycardia. [18]…”
Section: Discussionsupporting
confidence: 93%
“…[16] This agrees with a previous study that suggests that packed RBCs increase regional oxygen delivery and tissue surface pH. [17] This was relevant clinically in our study when we observed a statistically significant decrease in the heart rate of our infants after transfusion, suggesting that this decrease in heart rate was most probably explained by the migitation of tissue hypoxia and concomitant tachycardia. [18]…”
Section: Discussionsupporting
confidence: 93%
“…In a related study that directly assessed regional O 2 utilization and muscle metabolism, tissue pH improved after pRBC transfusion without altering peripheral blood flow consistent with improved O 2 delivery due to augmented RCM and O 2 content [29]. In contrast, tissue pH did not change after equivalent volumes of colloid infusion supporting the contention in the current report that these effects emerge from changes in hemoglobin and not from blood volume expansion per se [29].…”
Section: Discussionsupporting
confidence: 78%
“…Given this observed response to "booster" transfusion, it appears that real-time rSO 2 and FTOE monitoring revealed a reversible subclinical departure in the balance of oxygen delivery-to-consumption following quantitative iatrogenic phlebotomy in these patients before manifestation of any systemic clinical signs (e.g., tachycardia, metabolic acidosis, etc.) [4,20,29].…”
Section: Discussionmentioning
confidence: 99%
“…The failure to identify a change in the hematocrit is likely a result of our practice of administering booster-packed red-cell transfusions to all oxygen requiring ventilated patients to maintain their hematocrits at or approximately 40%. 40,41 Although, the changes in the absolute monocyte and lymphocyte counts were statistically significant at the 7-to 10-day point, they always remained within the range of published normal values. 36 No adverse effects could be attributed to these unintended study drug responses.…”
Section: Discussionmentioning
confidence: 75%